O conceito de ‘Comunidade de Destino’ na obra ‘Die Nationalitätenfrage und die Sozialdemokratie’ de Otto Bauer (1907) - Margis, Simone Maciel (2017)
The Master's Dissertationentitled "The Concept of Community of Destination in Otto Bauer's 'Die Nationalitätenfrage und die Sozialdemokratie' (1907), developed in the Research Line Frontier, Politicsa nd Society, linked to the Graduate Program in History of the University Federal University of Santa Maria and Research Projects "The Concept of Community of Destination in Otto Bauer's Die Nationaltätenfrage und die Sozialdemokratie" (1907) ", to the Research Group "Intellectual History in the 19th and 20th Centuries: Philosophy, Culture, Policy, coordinated by Prof. Carlos Henrique Armani, DR., with featured of a Capes/DS scholarship, aimed to carry out an internal analysis of Otto Bauer's work (1881-1938) entitled "Die Nationalitätenfrageund die Sozialdemokratie". Refers to the construction of the significant nation from a methodology proposed by the History of Ideas. In order, it was intended to expose Bauer's intentions about the formation of the complex hierarchical network of constitutive concepts of being-nation, whose intertwined identities of the concepts of Natural and Cultural Community culminate in what Bauer called "Community of Destination", represented by the will In the projection to a common end. Following the analysis, we also propose to analyze the temporal implications in the author's theory, in order to identify the use of temporality in its national perspective. Thus, we try to understand how Otto Bauer understood the national phenomenon from his textual corpus - both Bauer and related authors - as well as the temporal implications in his discourse.